Assessment of Skin Problems in Healthcare Personnel during COVID-19 Pandemic: A Cross-sectional Study from Central Vaccination Center - Kietkhongnatee, Jatakul; Chayangsu, Onjuta (Journal of The Department of Medical Services, 2024)
Background: During the coronavirus disease 2019 (COVID-19) pandemic, Thai government opened the Central Vaccination Center (CVC) for people to be vaccinated, so healthcare personnel had to apply extra personal protective equipment (PPE) during extended hours. This occurrence may be related to some dermatologic conditions. Objective: To determine the skin problems of healthcare workers operate at CVC and contributing factors. Methods: A cross-sectional descriptive study was performed by a random survey of healthcare personnel working at CVC from October 2021 to September 2022. Demographic data, job, hobby, type and duration of PPE usage, working hours, frequency and type of substance for hand washing, moisturizer application and dermatologic problems were collected from the questionnaire. The diagnosis of skin condition was performed by the researcher. Results: From a total of 406 healthcare personnel, the mean age was 34.8±10.8 years. Skin problems were observed in 291 persons (71.6%), the most common conditions were xerosis (66.7%), skin damage from pressure injury (63.9%), and acne vulgaris (60.1%), respectively. Younger age was a protective factor against skin problems (prevalence risk ratio; PRR = 0.98, p = .021). The vaccine injector had skin problems more than other jobs (PRR = 1.11, p = .038). N95 facial mask was a risk factor (PRR = 1.11, p = .004), whereas fabric mask was a protective factor for acne (PRR 0.84, p = .001). Using latex gloves with powder enhanced the risk of hand eczema (PRR = 1.15, p < .001). Hand washing with soap increased the risk of skin pruritus (PRR = 1.71, p = .022). Conclusion: Dermatologic problems in health workers are common during COVID-19 pandemic. The protective factors are younger age and wearing fabric mask. On the other hand, the risk factors include working as a vaccine injector, wearing an N95 mask, using latex gloves with powder, and hand wash with soap.